Resilience of national team student football players with different life values - Khokhlova, N. I.; Muller, O. Y.; Rodermel, T. A. (Theory and Practice of Physical Culture, 2024)
Objective of the study was to identify the multidimensional relationship between the levels of life values and resilience of student football players.